2012
DOI: 10.1103/physreva.85.050303
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement creation with negative index metamaterials

Abstract: We propose a scheme for creating of a maximally entangled state comprising two field quanta. In our scheme, two weak light fields, which are initially prepared in either coherent or polarization states, interact with a composite medium near an interface between a dielectric and a negative index metamaterial. Such interaction leads to a large Kerr nonlinearity, reduction of the group velocity of the light and significant confinement of the light fields while simultaneously avoiding amplitude losses of the incom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The generation and preservation of bipartite or multipartite quantum correlations have been widely studied both theoretically [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and experimentally [21][22][23][24][25][26] in recent years. Usually, people use of methods to create entanglement either indirect coupled quantum systems or direct coupled quantum systems [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The generation and preservation of bipartite or multipartite quantum correlations have been widely studied both theoretically [7][8][9][10][11][12][13][14][15][16][17][18][19][20] and experimentally [21][22][23][24][25][26] in recent years. Usually, people use of methods to create entanglement either indirect coupled quantum systems or direct coupled quantum systems [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…By using electromagnetically induced transparency (EIT), it was shown that the SPs have a very small attenuation. References [17,18] extended this scheme for obtaining a large crossphase modulation (CPM) and hence realizing large phase shifts or maximum entangled states of two optical pulses. However, to obtain low-loss SPs and large CPM predicted * gxhuang@phy.ecnu.edu.cn in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, to obtain low-loss SPs and large CPM predicted * gxhuang@phy.ecnu.edu.cn in Refs. [16][17][18], a very low room-temperature condition is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Metasurfaces can break the symmetry of quantum vacuum fluctuations and create a strong anisotropic quantum vacuum as experienced by a distant quantum emitter.…”
Section: Introductionmentioning
confidence: 99%